(untitled) (Journal of Comparative Research in Anthropology and Sociology, 2025)
In the context of the proliferation of anti-aging discourse on social media platforms, this study investigates how Romanian women aged between 49 and 80 relate to digital content that promotes aesthetic youth as an aspirational norm. Grounded on a sociological theoretical framework integrating capital theory (Bourdieu, 1986), neoliberal aesthetic governance (Rose, 1999; Gill, 2007) and age social constructionism (Gullette, 2018; Berger & Luckmann, 1966), the research analyzes data from a questionnaire administered to a sample of 110 women. The study explores the relationship between exposure to anti-aging content, its perceived realism and attitudes towards aging, highlighting processes of internalization, reflexive complicity and aesthetic resistance. Contingency analyses show that frequency of content viewing is correlated with perceptions of realism and attitudes towards ageing, while active engagement (like, comments) is associated with increased internalization of aesthetic norms. The results suggest, based on a small sample of 110 Romanian women, that social media may function as an algorithmic visibility regime that potentially amplifies neoliberal ideals of youth, while also indicating possible spaces for identity and counter-narrative negotiation. The study contributes to the digital sociology of ageing by exploring, within the limitations of a non-representative sample, how female ageing may not only be a biological process but also a symbolic territory of contestation and social resignification, where agency appears to be mediated by technological, affective, and discursive infrastructure.